La admisión de prueba en el proceso contencioso administrativo - Rojas Ortega, Alex (2021)
Administrative litigation consists of both written and oral stages, in which parties can offer evidence and judges conduct a legality analysis to determine its admissibility or rejection. This essay approaches the different types of evidence parties may submit, the different stages established within the process to submit evidence, and the consequences of not complying with them, regarding both the admission or rejection of evidence.